Antinutritional effects of the chitin-binding lectin from Microgramma vacciniifolia rhizome (MvRL) on Sitophilus zeamais. (September 2020) - Albuquerque, Lidiane Pereira de; Procópio, Thamara Figueiredo; Guedes, Caio César da Silva; Pontual, Emmanuel Viana; Paiva, Patrícia Maria Guedes; Napoleão, Thiago Henrique
Abstract: Sitophilus zeamais Motsch. (Coleoptera: Curculionidae) is one of the most common and destructive storage pests in the world and its control depends mostly on the utilization of synthetic pesticides. The hazards of synthetic chemicals to people and the environment, together with the development of resistance by the insects, stimulate the investigation of alternative methods. In the present study, we determined the effects of the ingestion of artificial diet containing the Microgramma vacciniifolia rhizome lectin (MvRL) on survival, feeding and nutrition of S. zeamais adults. MvRL was incorporated into the artificial diets at concentrations ranging from 10 to 130 mg/g. Mortality rate, ingested food and variation in the weight of the insects were determined after 7 days. In addition, the in vitro effects of MvRL on the activity of insect digestive enzymes were investigated. MvRL did not increase the mortality rates but disrupted the nutritional status of the insects since the biomass variation and efficiency in conversion of ingested food were negative. The lectin was able to inhibit in vitro β-glucosidase and α-amylase activities. In conclusion, MvRL showed anti-nutritional properties on S. zeamais adults, which may be due interference with digestive enzymes. MvRL may be useful as an additive or synergistic agent for reduced pest fitness by affecting the food conversion into biomass. Highlights: The effects of  Microgramma   vacciniifolia  rhizome lectin (MvRL) on  S.   zeamais were determined. MvRL was incorporated into the artificial diets at concentrations ranging from 10 to 130 mg/g. MvRL disrupted the nutritional status of the insects. The lectin inhibited  in vitro  β-glucosidase and α-amylase activities. The lectin inhibited  in vitro  β-glucosidase and α-amylase activities.